Simultaneous Determination of Hydroquinone, Catechol and Resorcinol with High Selectivity Based on Hollow Nitrogen-Doped Mesoporous Carbon Spheres Decorated Graphene. Issue 5 (30th March 2018) - Peng, Chang; Li, Zefan; Zhang, Xuemei; Zhou, Suya; Zhang, Wei; Liu, Xiaoying; Zhao, Peng
Abstract : For the first time, we have synthesized hollow nitrogen-doped mesoporous carbon spheres decorated graphene (NMC-G) and applied it in the simultaneous determination of hydroquinone (HQ) resorcinol (RC) and catechol (CC) in real samples. In the composite of NMC-G, hollow mesoporous carbon spheres possess high surface area and graphene have shown high electro-catalytic activity to many electroactive substances. As a result, the oxidation overpotentials of HQ, RC and CC decreased and the potential separations were 0.38, 0.49 and 0.11 V for CC and RC, RC and HQ, and HQ and CC, respectively. A linear response was obtained from 5 μM to 150 μM for the simultaneous determination of HQ, RC and CC, the linear equation was I - I0 = 0.7695 + 0.08751 C HQ for HQ, I - I0 = 0.00858 + 0.02243 C RC for RC and I - I0 = 0.5027 + 0.07829 C CC for CC, respectively. Furthermore, the concentration of HQ, RC, and CC were assayed in tap water samples, the recoveries were from 95.0% to 106.6%.